Symbolic Interactionism Between Students and Caregivers in Pesantren - Fajri, Barlian; Abdulghani, Naser Ali (Al-Jadwa: Jurnal Studi Islam, 2025)
Amidst the current wave of modernization, challenges arise in preserving the traditional values that form the foundation of pesantren (Islamic boarding school) education. This study aims to examine how symbolic interactions between students and caregivers at the Pesantren Darullughah Wadda’wah (Dalwa) in Pasuruan contribute to the formation of the students' character and identity. Using a qualitative approach with descriptive-analytical methods, data were obtained through participant observation, in-depth interviews, and documentation. The results of the study indicate that symbolic interactions manifested through symbols such as the call "Abuya," gestures of respect, and daily rituals shape the social world of students based on five main values: sincerity, honesty, devotion, togetherness, and wisdom. These values are reproduced consistently through daily practices and become pillars of character education based on Islamic values. This study contributes to the development of the sociology of Islamic education through symbolic interactionism between students and caregivers in pesantrens, while also emphasizing the relevance of pesantrens as educational institutions that are adaptive but still rooted in tradition and the meaningfulness of education.